Modelling of solar irradiance and daylight duration for solar-powered UAV sizing - Rajendran, Parvathy; Smith, Howard (Multi-Science Publishing, 2016)
Solar energy from the sun is the largest available renewable energy that enhances the endurance of a solar powered unmanned aerial vehicle. However, harnessing this solar power is a great challenge. This is due to having solar module system’s power output efficiency of only about 15–30%. However, a solar powered unmanned aerial vehicle has the potential to outperform a battery only operated unmanned aerial vehicle, especially when task being a pseudo satellite which requires long operating hours. The atmospheric conditions and geological locations undoubtedly the main cause for poor performance of these solar modules. In spite of its prolific improvement in solar cell efficiency over the years, the overall solar module system barely converts half of sun’s power into electricity. Therefore, this situation makes the current system unattractive to be widely used for energy harvesting. Recent attention has been focused not only on type of solar cells but on its positioning system. However, there were lack of understanding and research on the solar irradiance intensity and daylight duration’s effect on the power output. Therefore, a comprehensive model was developed to study on how the sun movement affects the solar module system’s performance. This simulation model has identified the daylight duration is more important in comparison to the available solar irradiance. Moreover, the higher the solar irradiance and daylight duration, the solar module system gives the most power output. The daylight duration also depends on the latitude where the higher the latitude gets, the longer the daylight duration. Besides, the longitudinal coordinates and elevation have minor effect on the daylight duration estimation. In other words, in summer, the northern hemisphere has more advantage compared to the southern hemisphere locations and vice versa.
Keywords: Solar irradiance; daylight; solar module; solar azimuth; tilt angle; path planning